ASPECTS OF THE OBESIDADE IN INFANCY (Fiep Bulletin - online, 2011)
The obesidade has been white of quarrel for diverse professionals compromissados with the health human being, since the excess of corporal fat can cause innumerable , hipertensivas cardiovascular, pulmonary illnesses, beyond causing injuries, breakings and reduction of mobility, and also psychological damages. Its etiology is multifactorial being, the sex, the age, the psychological environment, problems, physical inactivity, bad feeding and endócrinos problems, considered as main .causing agents of this phenomenon. How much to the origin, the obesidade can be classified as exógena and endogenous, how much to the size and number of the cells in hipertrófica and hiperplásica and finally how much to the distribution of the corporal fat in android and ginóide. Therefore, the intention of this research was to verify the main evidences of literature in what it says respect to the installation, causes and consequences of the obesidade in infancy, identifying main ways of control, treatment, and mainly the prevention. E understanding the importance of the movement as prevention of illnesses, being the movement in the somewhat born child in this phase of the life, this must be stimulated. In this in case that, the Physical Education as it disciplines curricular that it aims at the Education by means of the movement, that has the intention of assisting in the development of the form citizens that, these come to transform the reality in which they are inserted, must be assumen of the considered ways more efficient to help our children in the development of the conscience on the importance of a style of healthful life. In accordance with the inquiries in innumerable studies, can be concluded that practical of physical exercise the regular associate to a balanced feeding can contribute in the prevention of the infantile obesidade and reversion of the picture of obesidade in the great majority of the cases
Keywords: physical activity; prevention; style of life